2010
DOI: 10.1007/s00394-010-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxysterols on cell viability, inflammatory cytokines, VEGF, and reactive oxygen species production on human retinal cells: cytoprotective effects and prevention of VEGF secretion by resveratrol

Abstract: 7β-OH, 7KC, and 25-OH have cytotoxic, oxidative, inflammatory, and/or angiogenic activities on ARPE-19 cells. As Rsv has some protective effects against oxysterol-induced cell death and VEGF secretion it could be valuable in ARMD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 49 publications
6
75
0
Order By: Relevance
“…An interesting observation was that interstitial VEGF levels were lower (P ϭ 0.04 by paired t-test) in the nontraining group that had received resveratrol for 8 wk. This observation is in line with previous reports showing that resveratrol is able to reduce VEGF release from human endothelial and retinal cells in culture (10,63) and that resveratrol lowers hypoxia-induced VEGF release in human adipocytes (9). However, resveratrol did not seem to influence the amount of VEGF secreted during exercise, suggesting that the exercise-induced stimulus overruled the potential effect of resveratrol.…”
Section: Capillary-to-fiber Ratio and Vegfsupporting
confidence: 92%
“…An interesting observation was that interstitial VEGF levels were lower (P ϭ 0.04 by paired t-test) in the nontraining group that had received resveratrol for 8 wk. This observation is in line with previous reports showing that resveratrol is able to reduce VEGF release from human endothelial and retinal cells in culture (10,63) and that resveratrol lowers hypoxia-induced VEGF release in human adipocytes (9). However, resveratrol did not seem to influence the amount of VEGF secreted during exercise, suggesting that the exercise-induced stimulus overruled the potential effect of resveratrol.…”
Section: Capillary-to-fiber Ratio and Vegfsupporting
confidence: 92%
“…Lin reported that RSV protects against oxidized LDL-induced breakage of the blood-brain barrier . Limited evidence showed that RSV regulates VEGF level in vascular ECs; however, decreased VEGF level caused by RSV treatment was observed in gingival fibroblasts (Nunez et al 2010), retinal cells (Dugas et al 2010), tongue squamous cell carcinoma, and hepatoma cells (Zhang et al 2005). Based on these data, we hypothesized that RSV may regulate high-glucoseinduced hyperpermeability via VEGF pathway.…”
Section: Introductionmentioning
confidence: 83%
“…There is mounting evidence that treatment with 25-OHC and 7-ketoC up-regulates the production of a number of inflammatory mediators including IL-1a, IL-6, IL-8, monocyte chemoattractant protein-1 (MCP-1) and MIP-1b in a wide variety of cell types (Prunet et al, 2006;Joffre et al, 2007;Morello et al, 2009;Dugas et al, 2010;Mascia et al, 2010). However, the mechanisms underlying the proinflammatory response to oxysterols remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The oxysterols 25-OHC and 7-ketoC have previously been shown to promote proinflammatory cytokine expression in non-gestational tissues at concentrations ranging from 0.8 to 30 mg/ml (Dugas et al, 2010;Palozza et al, 2010). Due to this variability amongst different cell types, we sought to test a variety of concentrations to assess their effects on inflammation in trophoblasts.…”
Section: -Ohc and 7-ketoc Promote Proinflammatory Cytokine Productimentioning
confidence: 99%
See 1 more Smart Citation